Levantamiento geológico – estructural a escala 1:25000 de la zona sur de la parroquia Chuquiribamba, cantón y provincia de Loja. - Montaño Pullaguari, Estefanía Elizabeth (2021)
The main objective of this research work is to carry out the geological-structural survey at a scale of 1: 25000 of the southern area of the Chuquiribamba parish. The study area comprises an area of 35.66 km2; It is located in the South of Ecuador, in the province and canton of Loja, 41 km from the cantonal head to the northwest. Politically it limits the North with the parishes Gualel and Santiago; to the South with the Chantaco parish and the Catamayo canton; to the East with the parishes Santiago and Chantaco and; to the West with the Gualel parish and El Cisne parish. The geological - structural survey carried out in the southern zone of the parish, allowed to characterize eight lithological units: Gonzabal Unit, Tesalia Unit, Sayo Cruz Unit, Colluvial Deposit, Rhyolites, Rhyolitic Porphyry, Granodiorites and Diorites. In which, the Tesalia Unit covers the largest extension of territory with 18.19 km2, outcrops in the sectors of the same name; Tesalia Alto, Tesalia Bajo and the Guayllas and Saracapa neighborhoods; It is mainly made up of andesitic lavas, volcanic breccias, rhyolitic tuffs and dacitic tuffs, but basaltic andesites and rhyolites can be found to a lesser extent. Andesitic lavas have greenish-gray and dark gray colorations, aphanitic to porphyritic texture, whose mineralogical composition is characterized by hornblende and pyroxene minerals. Likewise, it is important to highlight that the granodiorite intrusive body comprises an area of 7.35 km2, being the second largest unit in the study area; they present an intermediate to felsic composition, they outcrop to the southwest of the study area in Loma Bain, finding themselves in contact with the Tesalia Unit; This intrusive body has a light gray color and black speckles, with a granular hypidiomorphic texture, of medium to coarse grain, whose mineralogical composition comprises approximately 45% plagioclase, 35% quartz, 15% altered potassium feldspars and 5% minerals. ferromagnesians such as hornblende and biotite. Regarding the structural geology, it was identified that the study area is deformed mainly by a system of faults located in the western part of the study area, which generally emerge in the streams: Tesalia, Tabla, Uritu Huasir; and lithological contact zones, have a preferential direction of W- E, NW - SE, NE - SW and whose lengths reach 3000 m. This fault system is made up of 10 inferred faults, 2 inferred normal faults and 1 observed reverse fault, formed by the various tectonic processes that have arisen over time. On the other hand, in the eastern part of the study area there are two faults, one observed and the other inferred: the first in a NW-SE direction limiting the SW margin of the rhyolitic porphyry and the second in a NE-SW direction, putting rocks in contact. volcanic acid composition with the volcanosedimentary sequences of the Gonzabal Unit, as well as folded structures such as anticlines and synclines and a family of joints with S52ºW direction, 80º inclination and NW dip direction.